2023
DOI: 10.4103/atm.atm_147_22
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the awareness of venous thromboembolism in the Saudi population

Abstract: BACKGROUND: Venous thromboembolism (VTE) causes significant morbidity and mortality. International studies have suggested poor public awareness of VTE, with a few data from Saudi Arabia. The aim of this study was to investigate the knowledge and awareness of VTE in the Saudi population. Awareness of other important diseases was also investigated to allow contextualization. METHODS: A cross-sectional survey study was conducted throughout Saudi Arabia from April to June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…where n is the sample size, Z is the level of confidence (95% confidence interval =1.96), P is the prevalence of VTE (1-2 per 1000 adults worldwide) [ 1 , 3 ], and e is the margin of error.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…where n is the sample size, Z is the level of confidence (95% confidence interval =1.96), P is the prevalence of VTE (1-2 per 1000 adults worldwide) [ 1 , 3 ], and e is the margin of error.…”
Section: Methodsmentioning
confidence: 99%
“…To upsurge global awareness of the thrombosis-related disease burden, starting in 2014, the International Society on Thrombosis and Haemostasis (ISTH) declared 13 October as the World Thrombosis Day [ 13 ]. A few studies in the Kingdom of Saudi Arabia have shed light on community awareness of VTE [ 2 , 3 , 14 ]; hence, people must be aware of this disorder as it may be a life-threatening disease [ 13 ]. This study aimed to assess the awareness and knowledge of VTE risk factors, manifestations, prevention, and treatment options among the general adult population of Dawadmi, Riyadh, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these few studies that identified various risk factors for mortality among critically ill Covid‐19 patients admitted to ICU in various countries, it remains necessary to investigate the association between the risk of VTE, blood hyperlactatemia and ICU mortality among these patients in Saudi Arabia. Because public awareness about VTE has been reported as poor in Saudi Arabia 13 . Therefore, this study investigated the association between VTE, blood hyperlactatemia and ICU mortality risk among critically ill patients with Covid‐19 in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Because public awareness about VTE has been reported as poor in Saudi Arabia. 13 Therefore, this study investigated the association between VTE, blood hyperlactatemia and ICU mortality risk among critically ill patients with Covid‐19 in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%